2023
DOI: 10.3390/ijerph20186721
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) as a Risk Factor for Cardiovascular Diseases: Pathophysiology and Treatment Perspectives

Pierandrea Vinci,
Filippo Giorgio Di Girolamo,
Emiliano Panizon
et al.

Abstract: Cardiovascular disease (CVD) is still a leading cause of morbidity and mortality, despite all the progress achieved as regards to both prevention and treatment. Having high levels of lipoprotein(a) [Lp(a)] is a risk factor for cardiovascular disease that operates independently. It can increase the risk of developing cardiovascular disease even when LDL cholesterol (LDL-C) levels are within the recommended range, which is referred to as residual cardiovascular risk. Lp(a) is an LDL-like particle present in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 200 publications
0
5
0
Order By: Relevance
“…Its serum level is associated with atherosclerotic cardiovascular diseases, including PAD. Previous studies have shown that Lp-a is a significant independent risk factor for PVD and is also associated with more severe forms of PVD in specific populations ( 57 59 ). Our study also indicated that LP-a is an important risk factor of PVD in T2DM, which is consistent with the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Its serum level is associated with atherosclerotic cardiovascular diseases, including PAD. Previous studies have shown that Lp-a is a significant independent risk factor for PVD and is also associated with more severe forms of PVD in specific populations ( 57 59 ). Our study also indicated that LP-a is an important risk factor of PVD in T2DM, which is consistent with the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…In predicting the onset and progression of heart disease, Apo-B/Apo-A1 has a greater predictive value than Apo-B or Apo-A1 alone [21]. In addition, elevated Lp(a) is an IRF for CAD and can increase the risk of cardiovascular events even in the presence of effective control of LDL-C [22]. APOE gene polymorphisms are markedly linked with lipid levels [23].…”
Section: Discussionmentioning
confidence: 99%
“…Significant scientific findings have elucidated Lp(a)'s role in the pathogenesis of aortic stenosis [9]. Enhanced Lp(a) levels are believed to be responsible for quicker aortic progression to stenosis, as reported by Tsimikas et al and Vinci et al, whose studies established clinically measurable parameters such as stenotic valve area and trans-valvular gradients [17]. Studies have also proven that Lp(a) plays an essential role in the onset of CAVD, which is one of the first steps in aortic stenosis formation [9,18].…”
Section: Pathophysiologymentioning
confidence: 95%
“…Research specifically addresses Lp(a) in relation to CVDs, especially aortic valve stenosis [17]. However, elevated Lp(a) is directly related to clinical parameters such as stenotic valve area and transvalvular gradients, which are involved in the progression of aortic stenosis.…”
Section: Pharmacological Managementmentioning
confidence: 99%
See 1 more Smart Citation